3D Confinement Strategy for Dendrite‐Free Sodium Metal Batteries. Issue 4 (24th March 2021) - Li, Zhaopeng; Zhu, Kunjie; Liu, Pei; Jiao, Lifang
Abstract: Sodium metal batteries (SMBs) are attracting extensive attention for large‐scale energy storage due to the abundant reserves and low cost of sodium. However, the inevitable side reactions and uncontrollable dendrite growth in SMBs result in a continuous deterioration of the electrochemical performance and induce serious safety concerns, which severely restrict its practical application in the future. Among various improvement strategies, the 3D confinement strategy demonstrates great potential for stabilizing the Na anode owing to its optimized ion/electron transportation, lower deposition overpotential, and superior structural stability. Herein, first, the recent progress in SMBs which use the 3D confinement strategy to improve the electrochemical cycling stability of Na anode are outlined, and the potential regulation mechanism, including the transport/deposition behavior of Na +, interface engineering, and some advanced characterization techniques, are summarized. Furthermore, critical challenges and new perspectives are emphasized in detail. This review provides a deeper insight to enable construct ion of more comprehensive and effective Na metal anodes for advanced SMBs. Abstract : Sodium dendrites, as the culprit of safety concerns, severely restrict the further development of sodium metal batteries. In this review, the 3D confinement strategy is summarized and its potential regulation mechanism is revealed. Owing to the improved Na + /electron transport, promoted structure stability, and optimized interface engineering, dendrite growth can be effectively suppressed by constructing novel 3D frameworks with high sodiophilicity.